2019
DOI: 10.1136/bcr-2019-229701
|View full text |Cite
|
Sign up to set email alerts
|

Forgotten pathogen: tetanus after gastrointestinal surgery

Abstract: A previously healthy 79-year-old woman underwent an urgent laparotomy and resection of a strangulated loop of small bowel. On the second postoperative day, she developed symptoms suspicious for postoperative tetanus. A transfer to the intensive care unit was necessary for aggressive supportive therapy. The patient required 5 months of intensive physiotherapy and rehabilitation and was successfully discharged home. New cases of tetanus have become rare in developed countries. This potentially lethal disease aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 8 publications
1
13
0
Order By: Relevance
“…The types of surgeries implicated in post-operative tetanus are mainly abdominal and gynecological, where there may be contact with the gastrointestinal tract, since 1–10 % of the population expresses the toxin in the feces [17] . Strypstein et al reported the case of a 79-year-old woman who developed tetanus two days after gastrointestinal surgery, even though amoxicillin and clavulanic acid were administered prophylactically [18] . Among published reports, none of the patients ended in fatal outcome and only one patient had sequelae such as motor and respiratory dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…The types of surgeries implicated in post-operative tetanus are mainly abdominal and gynecological, where there may be contact with the gastrointestinal tract, since 1–10 % of the population expresses the toxin in the feces [17] . Strypstein et al reported the case of a 79-year-old woman who developed tetanus two days after gastrointestinal surgery, even though amoxicillin and clavulanic acid were administered prophylactically [18] . Among published reports, none of the patients ended in fatal outcome and only one patient had sequelae such as motor and respiratory dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Though this is considered a clean surgery, the classic incubation period of eight days fits well. Recent literature is scant for tetanus following insertion of prosthetic material, but post-operative tetanus following orthopedic [11] and gastrointestinal surgery using prosthesis [12,13] has been reported. Alternative explanations include unsterile enoxaparin injections and previous puncture injuries that had healed upon presentation.…”
Section: Discussionmentioning
confidence: 99%
“…We found 19 case reports of tetanus following gastrointestinal procedures. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Table 1 outlines the findings and case summaries. In a study of 2422 patients with tetanus, 21.9% of patients did not have significant wound invasion, and it has been speculated that C. tetani may also invade the body through small abrasions.…”
Section: Discussionmentioning
confidence: 99%